Implementasi Kurikulum Merdeka Berbasis Projek Penguatan Profil Pelajar Pancasila (P5) Tema Gaya Hidup Berkelanjutan pada Kelas IV di Sekolah Dasar - Fauziah, Syifa; Fatayan, Arum (Jurnal Ilmiah Global Education, 2025)
The implementation of the Independent Curriculum is based on the Pancasila Student Profile Strengthening Project (P5) with the theme Sustainable Lifestyle in grade IV of Elementary School. This research was carried out with a qualitative approach through case studies. Data collection methods include observation, interviews, and documentation. This study provides a comprehensive analysis of the planning, implementation, and evaluation of P5 activities in elementary schools. The results of the study showed that P5 activities included making handicrafts from plastic waste, such as pencil holders and flower decorations, as well as planting kale in locations that were previously landfills. This activity aims not only to reduce plastic waste, but also to foster students' character, such as responsibility and concern for the environment.